Anthropometric Evaluation of NFPA 1977 Sizing System for U.S. Female Wildland Firefighters: A Contingency Table Analysis - Ziwen Qiu; Josephine Bolaji; Meredith McQuerry; Cassandra Kwon (Fire)
Ensuring proper sizing and fit for U.S. female firefighters’ personal protective clothing and equipment (PPE) is a crucial challenge for researchers and manufacturers. The National Fire Protection Association (NFPA) establishes design and performance standards in the U.S., with NFPA 1977 specifying sizing guidelines for wildland firefighting gear. However, the absence of an anthropometric database representing female firefighters limits the effectiveness of these standards. This research evaluates the effectiveness of NFPA 1977 sizing system by investigating whether correlated body measurements maintain internal consistency and provide data-driven recommendations for improvement. Anthropometric data from 187 U.S. female firefighters were analyzed to assess the 2016 and 2022 NFPA 1977 upper and lower torso sizing systems. Correlation analysis was performed between body measurements and corresponding sizes. Contingency tables presented proportion of participants accommodated. Results indicated significant correlations between chest and wrist measurements and sizes in the upper torso, though these were the only available measurements. In the lower torso, hip size strongly correlated with thigh and knee sizes. However, the system inadequately accommodates female firefighters with larger waist and hip measurements. Furthermore, rise sizes demonstrated inconsistent, weak relationships with hip circumference. Overall, the NFPA 1977 sizing requires revision to better serve U.S. female firefighters.